Virtual care in Ontario community health centres: a cross-sectional study to understand changes in care delivery - Sara Bhatti; Simone Dahrouge; Laura Muldoon; Jennifer Rayner (BJGP Open, 2022)
Background: There has been a large-scale adoption of virtual delivery of primary care as a result of the COVID-19 pandemic. Aim: In this descriptive study, an equity lens is used to explore the impact of transitioning to greater use of virtual care in community health centres (CHCs) across Ontario, Canada. Design & setting: A cross-sectional survey was administered and electronic medical record (EMR) data were extracted from 36 CHCs. Method: The survey captured CHCs‘ experiences with the increased adoption of virtual care. A longitudinal analysis of the EMR data was conducted to evaluate changes in health service delivery. EMR data were extracted monthly for a period of time before the pandemic (April 2019–February 2020) and during (April 2020–February 2021). Results: In comparison with the pre-pandemic period, CHCs experienced a moderate decline in visits made (11%), patients seen (9%), issues addressed (9%), and services provided (15%). During the pandemic period, an average of 54% of visits were conducted virtually, with telephone as the leading virtual modality (96%). Drops in service types ranged from 28%–82%. The distribution of virtual modalities varied according to the provider type. Access to in-person and virtual care did not vary across patient characteristics. Conclusion: The results demonstrate a large shift towards virtual delivery while maintaining in-person care. No meaningful differences were found in virtual versus in-person care related to patient characteristics or rurality of centres. Future studies are needed to explore how to best select the appropriate modality for patients and service types.